2007
DOI: 10.1038/nature05959
|View full text |Cite
|
Sign up to set email alerts
|

Conformational entropy in molecular recognition by proteins

Abstract: Molecular recognition by proteins is fundamental to almost every biological process, particularly the protein associations underlying cellular signal transduction. Understanding the basis for protein-protein interactions requires the full characterization of the thermodynamics of their association. Historically it has been virtually impossible to experimentally estimate changes in protein conformational entropy, a potentially important component of the free energy of protein association. However, nuclear magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
749
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(799 citation statements)
references
References 34 publications
33
749
2
4
Order By: Relevance
“…Similar to the literature 5,13,53,54 , the host-guest system under discussion showed a good linear correlation (correlation coefficient: r ¼ 0.98) between DH°and TDS° (Supplementary Fig. S4).…”
Section: Discussionsupporting
confidence: 67%
“…Similar to the literature 5,13,53,54 , the host-guest system under discussion showed a good linear correlation (correlation coefficient: r ¼ 0.98) between DH°and TDS° (Supplementary Fig. S4).…”
Section: Discussionsupporting
confidence: 67%
“…Such changes have been proposed to dominate the overall entropy of peptide binding and underlie the compensation of entropic and enthalpic contributions to peptide recognition. 2 In general, the unmodeled alternate conformations identified by Ringer help explain the observed conformational plasticity of the CaM binding site and provide testable hypotheses about where residual side-chain entropy is distributed in the protein.…”
Section: Low-occupancy Conformations Provide Functional Insights: Calmentioning
confidence: 97%
“…By studying calmodulin in complex with a series of different binding peptides, it was found that the apparent change in conformational entropy was linearly related to the change in the overall binding entropy. 60 This observation provided strong evidence that changes in protein conformational entropy can contribute significantly to the energetics of proteinligand association. In fact, empirical calibration of the NMR-derived conformational entropy suggested that the standard approach of summing up the individual contribution of each one of the experimentally accessible bond vectors may in fact underestimate the overall contribution of conformational entropy to the binding free energy.…”
Section: Dynamic Activation Of Protein Functionmentioning
confidence: 85%
“…Very interesting results on calmodulin have been particularly revealing about the role of conformational entropy in molecular recognition and allostery. 60,61 Calmodulin, a central player in calcium-mediated signaling, has been used as a model system to investigate the role of changes in fast (subnanosecond) internal dynamics and its associated conformational entropy in protein-ligand binding. By studying calmodulin in complex with a series of different binding peptides, it was found that the apparent change in conformational entropy was linearly related to the change in the overall binding entropy.…”
Section: Dynamic Activation Of Protein Functionmentioning
confidence: 99%